Table 1_The genetic landscape of congenital neutropenia in Poland: summary of the nationwide screening campaign.xlsx - Katarzyna Bąbol-Pokora (11710986) (2025)
This work summarizes 15 years of genetic research on neutropenia in the Polish pediatric cohort, explores the distribution and spectrum of disease-causing genetic variants associated with congenital neutropenia in Poland, and demonstrates the impact of a nationwide information campaign on increasing the efficiency of patient recruitment. The study included 126 patients with suspected congenital neutropenia recruited in 2008–2019 and 291 patients recruited in 2020–2023 as part of the FixNet project, which featured a nationwide information campaign. Molecular analyses were performed using Sanger sequencing (91 patients) and targeted next-generation sequencing (NGS) (326 patients) in a panel of neutropenia-related genes. The information campaign significantly increased the number of referred patients from 10.5 per year to 72.75 per year. Based on the results obtained, 102 patients belonging to 80 different families were diagnosed with severe congenital neutropenia (SCN) and neutropenia-related syndromes, the majority (43%) of whom harbored variants in the ELANE gene, including 12 novel ones. Most of the remaining cases were SBDS, CLPB, SRP54, and CXCR4 gene defects. This work describes the largest cohort of genetic variations associated with suspected congenital neutropenia (CN) in Poland and is an important contribution to the international SCN registry.